2004
DOI: 10.1111/j.1471-0528.2004.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomised controlled trial of laparoscopic uterine nerve ablation for women with chronic pelvic pain

Abstract: Objective To determine the effectiveness of laparoscopic uterine nerve ablation (LUNA) for chronic pelvic pain in women with endometriosis and women with no laparoscopic evidence of endometriosis. Design A prospective double-blind randomised controlled trial (RCT).Setting Single-centre, secondary-level gynaecology outpatient service and tertiary-level pelvic pain and endometriosis outpatient service in Auckland, New Zealand. Population One hundred and twenty-three women undergoing laparoscopy for investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 17 publications
(33 reference statements)
1
52
0
3
Order By: Relevance
“…However, due to the fact that its pathogenesis is complex, multifactorial and poorly understood, the pain can sometimes continue even though the apparent reason has been removed, and a non-specific treatment is needed [2,4,5,11,12]. A recent meta-analysis showed that the improvement effect of medical treatments on pain and QoL is limited and many medical treatments also bring significant side effects in many patients [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the fact that its pathogenesis is complex, multifactorial and poorly understood, the pain can sometimes continue even though the apparent reason has been removed, and a non-specific treatment is needed [2,4,5,11,12]. A recent meta-analysis showed that the improvement effect of medical treatments on pain and QoL is limited and many medical treatments also bring significant side effects in many patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…This procedure requires not only a greater degree of surgical skill but also carries a higher risk of intra-operative complications and long-term consequences. On the contrary, LUNA is known as a simple, feasible, and therefore relatively commonly performed surgical procedure [11]. For instance, in the UK, about 50% of gynecological endoscopists perform LUNA routinely during the surgical treatment of endometriosis [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic uterine nerve ablation (LUNA) and presacral neurectomy were also suggested as a treatment of pain symptoms. LUNA was found beneficial for dysmenorrhoea not associated with endometriosis (Johnson et al, 2004), while presacral neurectomy was found to reduce pain symptoms in endometriosis without significant side effects (Garcia Leon et al, 2003, Zullo et al, 2004.…”
Section: Peritoneal Endometriosis Surgical Management 731 Minimal Omentioning
confidence: 99%
“…Tem sido usada com melhor efi cácia em casos de dor pélvica crônica devido à endometriose severa associada à dismenorréia 54 .…”
Section: Tratamentounclassified